UTILIZATION OF KAOLIN FOR THRIPS PEST CONTROL IN CITRUS PLANTS - Rudi Cahyo Wicaksono; otto endarto (JURNAL AGRONIDA, 2019)
Citrus is one of the most consumed fruits. The projected demand for citrus fruit in 2015 - 2019 increased by 0.52% / kg / capita / year. However, citrus fruit production fluctuates every year. The average production of citrus fruits in 2011 - 2015 decreased by 1.49% per year. Decreased quality and quantity are due to pest attacks. Thrips attack the very young flower and fruit phase by injuring the surface of the fruit skin. The study was conducted from June to December 2017, in Glagahagung Village, Purwoharjo District, Banyuwangi Regency. The study used a randomized block design with four treatments using kaolin, surround, organim, and non-controlling, each repeated five times. The results of the study provided information that the use of kaolin continuously can suppress thrips pests up to 89.87%, while surround and organim supress up to 85.06% and 77.71% respectively, and can improve the quality of citrus fruits. Keywords: Kaolin, Surround, Thrips